A new metabotropic glutamate receptor agonist with in vivo anti-allodynic activity - Stanley, N.J.; Hutchinson, M.R.; Kvist, T.; Nielsen, B.; Mathiesen, J.M.; Brauner-Osborne, H.; Avery, T.D.; Tiekink, E.R.T.; Pedersen, D.S.; Irvine, R.; Abell, A.D.; Taylor, D.K. (Elsevier, 2010)
As part of the vital search towards improved therapeutic agents for the treatment of neuropathic pain, the central nervous system glutamate receptors have become a major focus of research. Outlined herein are the syntheses of two new biologically active 3'-cycloalkyl-substituted carboxycyclopropylglycines, utilizing novel synthetic chemistry. The reaction between substituted 1,2-dioxines and an aminophosphonate furnished the cyclopropane core in a single step with all required stereochemistry of pendant groups. In vitro binding assays at metabotropic glutamate receptors revealed selective activity. In vivo testing in a rodent model of neuropathic pain indicated one amino acid significantly and dose-dependently decreased mechanical allodynia. (C) 2010 Elsevier Ltd. All rights reserved.